Depression and anxiety are associated with abnormal nocturnal blood pressure fall in hypertensive patients. (August 2014) - Sunbul, Murat; Sunbul, Esra Aydin; Kosker, Selcen Dogru; Durmus, Erdal; Kivrak, Tarik; Ileri, Cigdem; Oguz, Mustafa; Sari, Ibrahim
Abstract Background: Previous studies have shown that depression and anxiety were independent risk factors for hypertension. Non-dipper hypertension is associated with higher cardiovascular mortality. The aim of this study was to evaluate the anxiety and depression scores in patients with dipper and non-dipper hypertension. Methods: The study sample consisted of 153 hypertensive patients. All patients underwent 24-h blood pressure monitoring. Patients were classified into two groups according to their dipper or non-dipper hypertension status. We evaluated results of the Hospital Anxiety and Depression Scale between groups. Results: Seventy-eight patients (38 male, mean age: 51.6 ± 12.5 years) had dipper hypertension while 75 patients (27 male, mean age: 55.4 ± 14.1 years) had non-dipper hypertension (p = 0.141, 0.072, respectively). Clinical characteristics were similar for both groups. Patients with non-dipper hypertension had significantly higher depression and anxiety scores compared to patients with dipper hypertension. Dipper and non-dipper status significantly correlated with anxiety (p: 0.025, r: 0.181) and depression score (p: 0.001, r: 0.255). In univariate analysis, smoking, alcohol usage, presence of diabetes, hyperlipidemia, anxiety score >8 and depression score >7 were predictors of dipper versus non-dipper status. In multivariate logistic regression analyses only depression score >7 was independent predictor of dipper versus non-dipper status (odds ratio: 2.74, confidence intervals: 1.41–5.37). A depression score of 7 or higher predicted non-dipper status with a sensitivity of 62.7% and specificity of 62.8%. Conclusion: Non-dipper patients have significantly higher anxiety and depression scores compared to dipper patients. Evaluation of anxiety and depression in patients with hypertension might help to detect non-dipper group and hence guide for better management.